How hospital survey teams function: An analysis of Care Quality Commission inspections of acute hospitals in England. Issue 2 (7th March 2018) - Boyd, Alan; Ross, Shilpa; Robertson, Ruth; Walshe, Kieran; Smithson, Rachael
Abstract : Purpose: The purpose of this paper is to understand how inspection team members work together to conduct surveys of hospitals, the challenges teams may face and how these might be addressed. Design/methodology/approach: Data were gathered through an evaluation of a new regulatory model for acute hospitals in England, implemented by the Care Quality Commission (CQC) during 2013-2014. The authors interviewed key stakeholders, observed inspections and surveyed and interviewed inspection team members and hospital staff. Common characteristics of temporary teams provided an analytical framework. Findings: The temporary nature of the inspection teams hindered the conduct of some inspection activities, despite the presence of organisational citizenship behaviours. In a minority of sub-teams, there were tensions between CQC employed inspectors, healthcare professionals, lay people and CQC data analysts. Membership changes were infrequent and did not appear to inhibit team functioning, with members displaying high commitment. Although there were leadership authority ambiguities, these were not problematic. Existing processes of recruitment and selection, training and preparation and to some extent leadership, did not particularly lend themselves to addressing the challenges arising from the temporary nature of the teams. Research limitations/implications: Conducting the research during the piloting of the new regulatory approach may have accentuated some challenges. There is scope for further research on inspection team leadership. Practical implications: Issues may arise if inspection and accreditation agencies deploy temporary, heterogeneous survey teams. Originality/value: This research is the first to illuminate the functioning of inspection survey teams by applying a temporary teams perspective.